ICT, financial access and gender inclusion in the formal economic sector: Evidence from Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
The study investigates the relevance of information and communication technology (ICT) in modulating the effect of financial access on female economic participation. Female economic participation is proxied by female labor force participation, financial access is measured with deposit and credit channels while ICT is proxied by mobile phone penetration, internet penetration and fixed broadband subscriptions. The focus of the study is on 48 African countries for the period 2004-2014 and the empirical evidence is based on Generalized Method of Moments. Policy thresholds are established at which, ICT modulates financial access to induce favourable effects on female economic participation. These policy thresholds are: (i) 160 mobile phone penetration (per 100 people) for the deposit channel and (ii) 2.166 and 0.75 fixed broadband subscriptions per 100 people for respectively, the deposit mechanism and credit channel. Overall the study supports the importance of ICT in moderating financial access for enhanced female economic participation.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Gender; ICT; Inclusive development